ANALISIS PERLINDUNGAN HUKUM KONSUMEN TERHADAP PEREDARAN MAKANAN TANPA SERTIFIKASI HALAL DAN TANGGUNG JAWAB PELAKU USAHA DIHUBUNGKAN DENGAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Dinda Aprilia; Farhan Asyhadi; Muhammad Abas (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The circulation of food without halal certification raises concerns for Muslim consumers in Indonesia. Although regulations such as Law No. 8 of 1999 concerning Consumer Protection and Law No. 33 of 2014 concerning Halal Product Assurance have regulated certification obligations, many products still circulate without halal assurance. The purpose of this study is to analyze consumer legal protection and the responsibilities of business actors regarding products without halal certification. This study uses a normative juridical method with a legislative and conceptual approach. The research shows that business actors have a legal responsibility to ensure product halalness and provide transparency of information to consumers. However, the implementation of legal protection still faces obstacles such as weak supervision and low business awareness. Strengthened supervision, education, and strict sanctions are needed to guarantee consumer rights and increase legal certainty regarding halal products.